Finding the right balance: implementation of public-private partnership in artemisinin-based combination therapy provision in Manokwari, Indonesia - Astri Ferdiana; Utsamani Cintyamena; Luthfi Azizatunnisa'; Edi Sunandar; Ari Probandari (Taylor & Francis Group, 2021)
Background Indonesia is the second country with the highest number of malaria cases in Southeast Asia. Private health providers including community pharmacies often become the first point of care for the population seeking malaria treatment; however, public-private partnerships for malaria control are not widely implemented. This paper explores the acceptability of a public-private partnership program on the provision of subsidized artemisinin-based combination therapies (ACTs) in community pharmacies from the perspectives of private health providers, patients, and program implementers. Methods The study was conducted in Manokwari District in West Papua Province, one of the highest endemic districts in Indonesia. Qualitative methods using interviews and focus group discussions (FGDs) were employed to explore the following dimensions of acceptability: affective attitude, burden, ethicality, intervention coherence, opportunity cost, perceived effectiveness, and self-efficacy. Study participants were program implementers, private health providers, and pharmacy clients. Audio-recorded interviews were transcribed and analyzed using thematic analysis. Secondary data on malaria cases and the use of ACTs reported by community pharmacies were also recorded. Results Only one-fourth of the total community pharmacies in Manokwari participated in the partnership, suggesting low coverage of the program. The proportion of malaria cases reported by community pharmacies increased from 6.9% in 2018 to 30.7% of cases. Most participants had a positive attitude towards the program, which might be associated with the perceived effectiveness of the partnership in improving access to ACTs. Despite the good understanding of the intervention by the participating pharmacies, limited involvement of private physicians often resulted in non-standardized treatment practices. The partnership also imposed a burden on private health providers in terms of human resources and time which entailed significant opportunity costs. A number of ethical issues might undermine the equity of access to ACTs. Conclusion Despite the positive attitude to the partnership, the perceived burden might outweigh the tangible benefits, posing threats to scaling up the intervention and sustainability. Innovations to simplify the administrative procedures in combination with performance-based incentives are needed to improve implementation. Engagement of patients and physicians is needed to increase the effectiveness of the partnership.